Responses to monetary policy shocks in the east and the west of Europe: a comparison - Marek Jarociński (European Central Bank (ECB), 2008)
This paper compares impulse responses to monetary policy shocks in the euro area countries before the EMU and in the New Member States (NMS) from central-eastern Europe. We mitigate the small sample problem, which is especially acute for the NMS, by using a Bayesian estimation that combines information across countries. The impulse responses in the NMS are broadly similar to those in the euro area countries. There is some evidence that in the NMS, which have had higher and more volatile inflation, the Phillips curve is steeper than in the euro area countries. This finding is consistent with economic theory.
Keywords: C11; C32; C33; E40; E52; 330; Bayesian estimation; exchangeable prior; Monetary policy transmission; Structural VAR; Geldpolitische Transmission; Schock; Bayes-Statistik; Schätzung; Panel; EU-Staaten; EU-Mitgliedschaft